Taxonomic review of the Agave potatorum Zucc. (Agavaceae) complex: new taxa and neotypification - García-Mendoza, Abisaí Josué (Instituto de Ecología, A.C., 2010)
The Agave potatorum complex, of group Hiemiflorae, is revised. Two new taxa from Oaxaca, Agave nussaviorum and A. nussaviorum subsp. deltoidea, are described and illustrated. The new species is compared with Agave seemanniana Jacobi and A. potatorum Zucc. Information concerning its distribution, ethnobotany, and phenology, and an identification key to the taxa of the complex are provided.